Minha escola transparente: uma análise comparativa do uso de dados governamentais abertos na educação básica no Brasil e Inglaterra - Santos, Otávio Albuquerque Ritter dos (2014)
This research attempts to analyze the effects of open government data on the administration and practice of the educational process by comparing the contexts of Brazil and England. The findings illustrate two principal dynamics: control and collaboration. In the case of control, or what is called the 'data-driven' paradigm, data help advance the cause of political accountability through the disclosure of school performance. In collaboration, or what is referred to as the 'data-informed' paradigm, data is intended to support the decision-making process of administrators through dialogical processes with other social actors.